REKONTRUKSI ATURAN TENTANG SENGKETA LINGKUNGAN HIDUP ATAS TANAH YANG TERKONTAMINASI MINYAK: Reconstruction Of The Rules On Environmental Disputes Over Oil-Contaminated Land - Suharja, Mohamad (Jurnal Globalisasi Hukum., 2024)
Whereas environmental disputes are suspected to occur in areas where there are mining activities, etc., so that the Government is appropriate and supervises the resolution of environmental disputes. Whereas the legal regulations for environmental settlement before the Claimants file an environmental lawsuit, based on the Ministerial Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No. P.22/MENLHK/SETJEN/SET.1/3/2017 Concerning Procedures for Managing Complaints of Alleged Environmental Pollution and/Or Destruction and/Or Forest Destruction ("Ministry of Environment and Forestry Regulation No. P.22/MENLHK/SETJEN/SET.1 /3/2017"), which in essence, claimants who are suspected of environmental pollution having occurred are obliged to make a complaint either directly or indirectly, but according to the author, many people still don't know about the information for making a complaint based on the Minister of Environment and Forestry Regulation. So the role of the government is needed to socialize these regulations. Then many people in the community are trying to directly file an environmental lawsuit with the relevant District Court, either a lawsuit for compensation or a lawsuit for environmental restoration, which is clear and evident that the community has not complied with the procedures for resolving environmental disputes based on the relevant legal regulations, which the community must make a complaint first, either directly or indirectly. So, according to the author, many parties suffer losses due to ignorance regarding environmental settlement procedures, both entrepreneurs and society. So according to the author, the Government, especially the Ministry of Environment and Forestry, needs to carry out outreach to the community, especially to people who live or whose business activities are close to mining activities, so that the community knows the correct steps if it is suspected that environmental pollution has occurred, so that it becomes a serious problem. which results in the environment being polluted and posing a threat to the survival of flora and fauna, as well as causing both material and immaterial losses to the community.